2022
DOI: 10.1002/adfm.202208751
|View full text |Cite
|
Sign up to set email alerts
|

Molten Salt Driven Conversion Reaction Enabling Lithiophilic and Air‐Stable Garnet Surface for Solid‐State Lithium Batteries

Abstract: current density of 1.2 mA cm −2 . Furthermore, the solid LiCoO 2 /Li cell with the modified garnet delivers a discharge capacity of 130 mAh g −1 at 30 °C, accompanied by a capacity retention of 81% after 150 cycles. This study proposes a promising solution for improvement of air stability and interfacial compatibility of garnet using facile molten salt treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
50
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 69 publications
1
50
0
1
Order By: Relevance
“…Various strategies have been applied to improve the interface compatibility between Li metal and LLZO. For example, SnN x , [ 39 ] Al 2 O 3 , [ 40 ] Ge, [ 41 ] Sb, [ 42 ] Cu 3 N, [ 43 ] graphite, [ 44 ] Ga, [ 45 ] Li 2 PO 2 F 2 , [ 46 ] NH 4 H 2 PO 4 , [ 47 ] and Li 3 PO 4 [ 48 ] have been used to reduce the interface resistance between LLZO and Li metal anode. In addition, the surface energy of Li metal can be changed by alloying to get a better wettability to LLZO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various strategies have been applied to improve the interface compatibility between Li metal and LLZO. For example, SnN x , [ 39 ] Al 2 O 3 , [ 40 ] Ge, [ 41 ] Sb, [ 42 ] Cu 3 N, [ 43 ] graphite, [ 44 ] Ga, [ 45 ] Li 2 PO 2 F 2 , [ 46 ] NH 4 H 2 PO 4 , [ 47 ] and Li 3 PO 4 [ 48 ] have been used to reduce the interface resistance between LLZO and Li metal anode. In addition, the surface energy of Li metal can be changed by alloying to get a better wettability to LLZO.…”
Section: Introductionmentioning
confidence: 99%
“…The lithium symmetric battery could stably run 1000 h at 0.1 mA cm −2 . [ 47 ] How to further enhance the CCD and the high‐rate capability of SSBs as well as improve the long‐term cycling stability is still a big challenge for garnet‐type SSEs. In addition, the storage instability of garnet‐type SSEs in the air is also a critical issue in practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…To solve the above problems, one effective approach is to modify the LLZTO surface with lithiophilic layers, such as CoO, 16 Ga, 17 MgF 2 , 18 Li 3 PO 4 19,20 etc. , so as to adjust the wettability between the Li anode and LLZTO, and further improve the interfacial contact.…”
Section: Introductionmentioning
confidence: 99%
“…12 The poor and loose contact and huge ASR (500-3000 O cm 2 ) at the anode side interface will lead to rapid growth of lithium dendrites and even short circuit of the batteries, which has become one of the main culprits in the practical applications of SSLMBs. [12][13][14][15] To solve the above problems, one effective approach is to modify the LLZTO surface with lithiophilic layers, such as CoO, 16 Ga, 17 MgF 2 , 18 Li 3 PO 4 19,20 etc., so as to adjust the wettability between the Li anode and LLZTO, and further improve the interfacial contact. Recently, some reports indicated that the integration of functional components into molten Li to synthesize CLA was also highly effective to improve the wettability, such as graphite, 21 BN, 22 AlF 3 23 or Si 3 N 4 24 and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, long-term cycling will lead to lithium dendrite growth at the solid electrolyte grain boundaries and cause electrolyte failure and short-circuit the battery. The most direct way to solve wettability is to use artificial SEI layers or alloys of lithium metal with different metal elements , or composites with polymers to the solid composite electrolyte to change the mechanical properties of the electrolyte. Most of the artificial SEI layers are modified with Li 3 N, LiCl, LiF, , and other materials for interface layer modification, which improves the wettability between the electrolyte and lithium metal layer. The alloy part is quite broad.…”
Section: Introductionmentioning
confidence: 99%